Association Between Extent of Stent-Graft Coverage and Thoracic Aortic Remodeling After Endovascular Repair of Type B Aortic Dissection. (April 2020) - Xue, Yan; Ge, Yangyang; Ge, Xiaohu; Miao, Jianhang; Fan, Weidong; Rong, Dan; Liu, Feng; Liu, Xiaoping; Guo, Wei
Purpose: To examine the association between the extent of stent-graft coverage and thoracic aortic expansion after thoracic endovascular aortic repair (TEVAR) for type B aortic dissection.Materials and Methods: A retrospective analysis was conducted of 201 patients (mean age 52.4±11.5 years; 178 men) with acute (135, 67.2%) or chronic (66, 32.8%) type B aortic dissection who underwent TEVAR at 4 medical centers. The mean stent-graft length was 157.1±33.3 mm. The percentage of stented descending aorta (PSDA) represented the extent of stent-graft coverage. After using restricted cubic smoothing spline plots to confirm the roughly linear relationship between PSDA and the risk of thoracic aortic expansion, patients were stratified into 2 groups on the median PSDA: the lower group (≤31.3%) and the higher group (>31.3%). Thoracic aortic expansion was defined as a ≥20% increase in the total thoracic aortic volume on the most recent postoperative computed tomography angiography scan compared with the preoperative measurement. The Kaplan-Meier method was used to estimate the cumulative freedom from thoracic aortic expansion after TEVAR; estimates are given with the 95% confidence interval (CI). A multivariable Cox proportional hazards model was used to analyze any independent association of the PSDA as a continuous or categorical variable with the risk of thoracic aortic expansion; results are presented as the hazard ratio (HR) and 95% CI.Results: No patients developed symptoms of spinal cord ischemia during hospitalization. Over a median 12.4 months of imaging follow-up, 34 (16.9%) patients developed thoracic aortic expansion. The estimate of freedom from thoracic aortic expansion at 12 months for the overall PSDA was 84.0% (95% CI 77.8% to 88.6%); between the groups, the freedom from thoracic aortic expansion estimate for the PSDA ≤31.3% group was significantly lower than in the higher group (p=0.032). Regression analysis showed no significant association between the risk of thoracic aortic expansion and the PSDA as a continuous variable (HR 0.97, 95% CI 0.91 to 1.03, p=0.288); however, analyzing the PSDA as a categorical variable indicated a significantly lower risk of thoracic aortic expansion for the PSDA >31.3% group (HR 0.46, 95% CI 0.22 to 0.95, p=0.036) after adjusting for a variety of demographic and anatomical characteristics.Conclusion: More extensive stent-graft coverage appears to improve thoracic aortic remodeling after TEVAR. However, the clinician should balance the benefit of extensive stent-graft coverage and its related risk of spinal cord ischemia.